Hepatocyte β‐catenin loss is compensated by Insulin‐mTORC1 activation to promote liver regeneration. Issue 5 (17th May 2023) - Hu, Shikai; Cao, Catherine; Poddar, Minakshi; Delgado, Evan; Singh, Sucha; Singh‐Varma, Anya; Stolz, Donna Beer; Bell, Aaron; Monga, Satdarshan P.
Abstract : Background and Aims: Liver regeneration (LR) following partial hepatectomy (PH) occurs via activation of various signaling pathways. Disruption of a single pathway can be compensated by activation of another pathway to continue LR. The Wnt–β‐catenin pathway is activated early during LR and conditional hepatocyte loss of β‐catenin delays LR. Here, we study mechanism of LR in the absence of hepatocyte‐β‐catenin. Approach and Results: Eight‐week‐old hepatocyte‐specific Ctnnb1 knockout mice (β‐catenin ΔHC ) were subjected to PH. These animals exhibited decreased hepatocyte proliferation at 40–120 h and decreased cumulative 14‐day BrdU labeling of <40%, but all mice survived, suggesting compensation. Insulin‐mediated mechanistic target of rapamycin (mTOR) complex 1 (mTORC1) activation was uniquely identified in the β‐catenin ΔHC mice at 72–96 h after PH. Deletion of hepatocyte regulatory‐associated protein of mTOR (Raptor), a critical mTORC1 partner, in the β‐catenin ΔHC mice led to progressive hepatic injury and mortality by 30 dys. PH on early stage nonmorbid Raptor ΔHC ‐β‐catenin ΔHC mice led to lethality by 12 h. Raptor ΔHC mice showed progressive hepatic injury and spontaneous LR with β‐catenin activation but died by 40 days. PH on early stage nonmorbid Raptor ΔHC mice was lethal by 48 h. Temporal inhibition of insulin receptor and mTORC1 in β‐catenin ΔHC or controls after PH was achieved by administration of linsitinib at 48 h or rapamycin at 60 h post‐PH and completely prevented LR leading to lethality by 12–14 days. Conclusions: Insulin‐mTORC1 activation compensates for β‐catenin loss to enable LR after PH. mTORC1 signaling in hepatocytes itself is critical to both homeostasis and LR and is only partially compensated by β‐catenin activation. Dual inhibition of β‐catenin and mTOR may have notable untoward hepatotoxic side effects. Abstract :